CONTINENTAL THERMAL AND TECTONIC REGIMES DURING THE ARCHEAN - England, P; Bickle, M (1984)
Describes how metamorphic pressures estimated from mineral assemblages in Archaean high-grade terrains may be used to constrain geothermal regimes in the Archaean continental crust. Discusses results, which imply that Archaean continental thermal regimes were similar to present-day ones. These observations, together with the common interpretation of komatite melting temperatures as being representative of Archaean upper mantle temperatures, are inconsistent with earth thermal histories based on parameterized convection calculations. The force per unit length of orogenic belt required to maintain the elevation contrasts implied by the pressure estimates is similar in magnitude to present-day driving forces for plate motion. -after Authors